What hides behind the rate of unemployment? Micro evidence from Norway - Knud Røed; Tao Zhang (University of Oslo, Department of Economics, 1999)
Building on a complete account of registered unemployment spells in Norway, we study how the composition of unemployment has developed over the last ten years. The total volume of unemployment has become more unequally distributed than before, but it is difficult to identify the `losers' in terms of observed characteristics. There are no signs of low-education workers doing systematically worse. The most conspicuous change with respect to observed characteristics is that the relative outflow rates for older workers have deteriorated sharply.
Keywords: 330; Arbeitslosigkeit; Norwegen